2011
DOI: 10.1017/s1041610211001220
|View full text |Cite
|
Sign up to set email alerts
|

Revised NIA-AA criteria for the diagnosis of Alzheimer's disease: a step forward but not yet ready for widespread clinical use

Abstract: In clinical medicine, diagnostic criteria are not only useful everyday tools for the practicing physician, but also represent a conceptual concentrate of the understanding of the etiology and pathophysiology of diseases at a given point in time. Although different sets of diagnostic criteria for Alzheimer's disease (AD) have been developed, the most widely used and best validated by clinico-pathological study to date are the NINCDS-ADRDA (National Institute of Neurological and Communicative Disorders and Strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…In doing so, significant relationships between PiB-PET and FLAIR intensities could be observed for right and left Hippocampus, Brainstem and also a small region including left Basal Ganglia vessels. As the FLAIR contrast reflects a wide spectrum of pathological brain-tissue alterations associated with regional edema (Young et al, 2008; Neema et al, 2009; Carlson et al, 2011), our finding is consistent with earlier reports on signature-regions of AD primarily affected by age-related neurodegeneration: The Hippocampus has been shown by numerous studies to be particularly sensitive to aging related brain change and AD in particular (de Leon et al, 1989; Frisoni et al, 2011; Serrano-Pozo et al, 2011) and neurodegenerative processes can be observed in gray matter nuclei located in Brainstem and Basal Ganglia (Iseki et al, 1989; Parvizi et al, 2001; Simic et al, 2009; Braak and Del Tredici, 2012; Brothers et al, 2013). Notably, significant relationships with FLAIR intensity were not determined by brain regions with highest PiB retention, which may support considerations on pathological relevance of subtle increases of Aβ in vulnerable brain regions (Mormino et al, 2012; Lowe et al, 2014), potentially mediated by additional factors that may determine resilience of distinct neuronal populations (Steffener and Stern, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In doing so, significant relationships between PiB-PET and FLAIR intensities could be observed for right and left Hippocampus, Brainstem and also a small region including left Basal Ganglia vessels. As the FLAIR contrast reflects a wide spectrum of pathological brain-tissue alterations associated with regional edema (Young et al, 2008; Neema et al, 2009; Carlson et al, 2011), our finding is consistent with earlier reports on signature-regions of AD primarily affected by age-related neurodegeneration: The Hippocampus has been shown by numerous studies to be particularly sensitive to aging related brain change and AD in particular (de Leon et al, 1989; Frisoni et al, 2011; Serrano-Pozo et al, 2011) and neurodegenerative processes can be observed in gray matter nuclei located in Brainstem and Basal Ganglia (Iseki et al, 1989; Parvizi et al, 2001; Simic et al, 2009; Braak and Del Tredici, 2012; Brothers et al, 2013). Notably, significant relationships with FLAIR intensity were not determined by brain regions with highest PiB retention, which may support considerations on pathological relevance of subtle increases of Aβ in vulnerable brain regions (Mormino et al, 2012; Lowe et al, 2014), potentially mediated by additional factors that may determine resilience of distinct neuronal populations (Steffener and Stern, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the diagnostic value of biomarkers may differ according to the disease stage. Therefore, the refinement of biomarker algorithms for the NIA-AA criteria constitutes a further challenge [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, we started this study in June 2009. The revised criteria require the examination of multiple biomarkers, including the need for a positron emission tomography (PET) examination, and the widespread clinical adoption of the revised criteria remains controversial 14. Thus, we did not adopt the revised criteria that were updated in 2011.…”
Section: Methodsmentioning
confidence: 99%